Nonlinear Volterra Integral Equation of the Second Kind and Biorthogonal Systems. (11th July 2010) - Berenguer, M. I.; Gámez, D.; Garralda-Guillem, A. I.; Serrano Pérez, M. C.
Abstract : We obtain an approximation of the solution of the nonlinear Volterra integral equation of the second kind, by means of a new method for its numerical resolution. The main tools used to establish it are the properties of a biorthogonal system in a Banach space and the Banach fixed point theorem.